Binary phase shift keying simulation with MATLAB and SIMULINK - Africa, Aaron Don M. (Animo Repository, 2020)
© 2020, World Academy of Research in Science and Engineering. All rights reserved. Digital Communication follows one fundamental concept and it is the transfer of information from one point to another over an analog channel. In our modern society there is one method which is versatile and widely used in transferring digital data and this method is called Digital Phase Modulation. In Digital Phase Modulation it is possible to use discrete values in the carrier frequency or amplitude in order to represent their values in ones and zeros. Given this possibility, it can be concluded that it is also possible to represent digital data using phase. Such technique is called Phase Shift Keying. The easiest approach to Phase Shift Keying is the Binary Phase Shift keying or BPSK. In Binary Phase Shift Keying, hinted from the keyword binary, it uses only two phases with each used for logic high and logic low which can be represented with a minimum and maximum value of 0 degrees for logic low and 180 degrees for logic high. This Modulation Technique utilizes a balance modulator which consists of a carrier sine wave and a binary sequence which is to be used as input in order to generate the Phase Shift Keying Output desired.